Performance analysis of the laboratories in the natural water microbiological analyses proficiency tests performed by the Rio Grande do Sul metrological network - Pizzolato, Morgana; Reis, Christine da Silva; Ribeiro, José Luis Duarte (Revista Gestão da Produção Operações e Sistemas, 2008)
This article deals with the performance of testing laboratories in proficiency testing (EP) conducted by the NetworkMetrológica of Rio Grande do Sul (RMRS). The EP are used by laboratories, clients, accreditation bodiesand regulatory authorities as a tool for control and verification of the technical capacity of the laboratory. TheRMRS, non-profit technical association, has been promoting since 1997 the implementation of programs for thetesting of proficiency (PEP). In 2007, fourteen EP will be promoted by RMRS. Among them, destaca PEP in microbiologicalanalysis of natural waters, which is the only one in Brazil, which has the scope to microbiologicalanalysis of natural waters. This article presents the trend of the results obtained by the laboratories participatingin the PEPs RMRS of microbiological analysis in natural waters over the years.Keywords: tests of proficiency (EP), performance, testing laboratories, microbiological analysis of natural waters.